Criteria for selecting actors for the value co-creation in startups - Bonamigo, Andrei; da Silva, Adrianne Alves; da Silva, Beatriz Pereira; Werner, Steffan Macali (The Journal of business & industrial marketing, 2022)
Purpose The purpose of this paper is to identify the main criteria for selecting actors to compose these business platforms and addressing the co-creation of value and improve the performance of startups. Design/methodology/approach The methodology is based on the search for key factors for the selection of actors and the understanding of co-creation of value and the concept of startups. The content of this paper is substantiated on an extensive review of the literature related to the subjects’ value-cocreation and new startups, and the review is based on the articles found in the databases of Ebsco, Emerald, Science Direct, Scopus, Village and Web of Science. Findings This paper identifies the main key-factors found in the literature for selecting actors to co-create value in startups and organizes the findings in five categories: value creation, interaction, actor behavior, client and partnership. It also presents the possibility of future research that will be able to put the study in practice. Research limitations/implications The results of this research have not been tested empirically, which opens the door for future studies that can prove the effectiveness of the findings. It is also important to mention that there are few articles in the literature that directly address this topic, and some definitions of actor/co-creation of value/business model may also change. Practical implications The selection criteria of the actors listed are useful for service entrepreneurs and managers to assist in decision-making at the stage of choosing their partners for value co-creation in startups. Furthermore, it involves mitigating waste in startups and maximizing the economic gains of partners through value co-creation in startups. Originality/value This study is one of the first attempts to recognize the key factors for selecting actors to co-create value in startups, aiming at their success in the market.